Team Learning Ditinjau dari Team Diversity dan Team Efficacy - Vivi Gusrini Rahmadani Pohan; Djamaludin Ancok (Faculty of Psychology, Universitas Gadjah Mada, 2010)
This research attempted to observe team learning from the level of team diversity and team efficacy of work teams. This research used an individual level of analysis rather than the group level. The team members measured the level of team diversity, team efficacy and team learning of the teams through three scales, namely team learning scale, team diversity scale, and team efficacy scale. Respondents in this research were the active team members in a company, PT. Alkindo Mitraraya. The total of the respondents were 70. Collected data were examined by using multiple regression analysis. Based on the hypothesis, it can be concluded that the team diversity and team efficacy can be used as indicators to predict the arousal of team learning level in teams (fcount = 5.924; p=0.004 or p < 0.05) and the value of adjusted r square = 0.125. Moreover, the result demonstrated that team diversity made a significant contribution to team learning level (r = 0.105; p < 0.05) while on the other hand, team efficacy did not affect team learning significantly. The equation of the regression line for team learning on team diversity and team efficacy was team learning = 30.362 + (0.377 team diversity) + (0.187 team efficacy). Suggested areas for future research were to confirm this research model using the team level analysis, to thoroughly determine the type of teams and to do research in the self‐managed team‐based organizations.